Mechanistic insights into carbamate formation from CO2 and amines: the role of guanidine–CO2 adducts. Issue 20 (22nd September 2021) - Mannisto, Jere K.; Pavlovic, Ljiljana; Tiainen, Tony; Nieger, Martin; Sahari, Aleksi; Hopmann, Kathrin H.; Repo, Timo
Abstract : This work explores the reactivity of a reversible superbase–CO2 zwitterion, which can be used as a stoichiometric source of CO2 . Abstract : Capture of CO2 by amines is an attractive synthetic strategy for the formation of carbamates. Such reactions can be mediated by superbases, such as 1, 1, 3, 3-tetramethylguanidine (TMG), with previous implications that zwitterionic superbase–CO2 adducts are able to actively transfer the carboxylate group to various substrates. Here we report a detailed investigation of zwitterionic TMG–CO2, including isolation, NMR behavior, reactivity, and mechanistic consequences in carboxylation of aniline-derivatives. Our computational and experimental mechanistic analysis shows that the reversible TMG–CO2 zwitterion is not a direct carboxylation agent. Instead, CO2 dissociates from TMG–CO2 before a concerted carboxylation occurs, where the role of the TMG is to deprotonate the amine as it is attacking a free CO2 . This insight is significant, as it opens a rational way to design new synthesis strategies. As shown here, nucleophiles otherwise inert towards CO2 can be carboxylated, even without a CO2 atmosphere, using TMG–CO2 as a stoichiometric source of CO2 . We also show that natural abundance 15 N NMR is sensitive for zwitterion formation, complementing variable-temperature NMR studies.